If we square a number and then take the square root of the result, then the output is the original number. Here are some examples:
(3 ⋅ 3)^(1 / 2) = 9^(1/2) = 3
(125 ⋅ 125)^(1 / 2) = 125
(x + 3 ⋅ x + 3)^(1 / 2) = x + 3
High-Level Proof
(x⋅x) = x2, so
x⋅x^1/2 = x21/2
We claim that
x21/2 = x(2 ⋅ 1/2)
2 ⋅ 1/2 is 1, so x(2 ⋅ 1/2) == x
if x ⋅ x = x2, then (x ⋅ x)(1 / 2) = (x2)(1 / 2) if 2 ⋅ (1 / 2) = 1, then x(2 ⋅ (1 / 2)) = x1 if the following are true: then a = e Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.
Quiz (1 point)